Partial weight bearing and long-term survival outcomes in extracapsular hip fractures treated with trochanteric Gamma3 nails - Carlos Hernández-Pascual; José Ángel Santos-Sánchez; Jorge Hernández-Rodríguez; Carlos Fernando Silva-Viamonte; Carmen Pablos-Hernández; Pablo Alonso-Rodríguez; José Antonio Mirón-Canelo (BMC Musculoskeletal Disorders)
Abstract Background Benefits of partial weight bearing (PWB) in operated extracapsular hip fractures (ECF) have not been proved. We have assessed influence of PWB on long-term survival and the final mobility achieved, dependence and mortality-related factors. Methods Retrospective cohort study of osteoporotic ECF in ≥ 65-year-old patients who underwent surgery with trochanteric Gamma3 nails in 2014 (n = 218), followed in the long-term (consolidation or stabilisation). According to Baumgaertner-Fogagnolo classification (138 good, 71 acceptable and 9 poor) a postoperative protocol was applied. 116 cases bore weight before discharge (Immediate Partial Weight Bearing, IPWB = 116; Not-IPWB = 102), and 118 did it after a month (Early PWB, EPWB = 118; Not-EPWB = 100). Variables were collected from medical records and complementary studies. We used FMS (Fracture Mobility Score) and the National Mortality Database from the Spanish Ministry of Health at > 5 years. EPWB and Not-EPWB were comparable, except for hospital stay and dependence. We used the Cox method for mortality. < 0.05 p-values were significant. Results Survival improved in IPWB earlier than in EPWB, although there was no statistical significance. The final FMS was significantly favourable only in EPWB. Not-EPWB showed greater dependence. Age (per year of increment), moderate Charlson comorbidity index (not age-modified) and greater immediate post-operative estimated blood loss were independent factors for mortality, but we did not find radiological factors implied. Conclusions Postoperative PWB in ECF may increase mid-term and long-term survival rates, but considerably delayed in EPWB. Only EPWB improved final mobility. Not-EPWB presented with greater dependence. Only clinical factors were independently related to mortality, but no radiological factors were.